Muscle activation does not increase after a fatigue plateau is reached during 8 sets of resistance exercise in trained individuals - Finn, H. T.; Brennan, S. L.; Gonano, B. M.; Knox, M. F.; Ryan, R. C.; Siegler, J. C.; Marshall, P. W. M. (The Journal of Strength and Conditioning Research, 2014)
The premise of eliciting the greatest acute fatigue is accepted and used for designing programs that include excessive, potentially dangerous volumes of high-intensity resistance exercise. There is no evidence examining acute fatigue and neuromuscular responses throughout multiple sets of moderate-to-high intensity resistance exercise. Fifteen resistance-trained male subjects performed a single exercise session using 8 sets of Bulgarian split squats performed at 75% maximal force output. Maximal force output (N) was measured after every set of repetitions. Electromyographic (EMG) activity of vastus lateralis was monitored during all force trials and exercise repetitions. Repetitions per set decreased from the first to the third set (p < 0.001). Maximal force output decreased from preexercise to set 4 (p < 0.001). Electromyographic amplitudes during exercise did not change. Secondary subgroup analysis was performed based on the presence, or not, of a fatigue plateau (<5% reductions in maximal force output in subsequent sets). Nine participants exhibited a fatigue plateau, and 6 did not. Participants who plateaued performed less first-set repetitions, accrued less total volume, and did not exhibit increases in EMG amplitudes during exercise. Initial strength levels and neuromuscular demand of the exercise was the same between the subgroups. These data suggest that there are individual differences in the training session responses when prescribing based off a percentage of maximal strength. When plateaus in fatigue and repetitions per set are reached, subsequent sets are not likely to induce greater fatigue and muscle activation. High-volume resistance exercise should be carefully prescribed on an individual basis, with intrasession technique and training responsiveness continually monitored.